Nicotine and neuronal nicotinic acetylcholine receptors: unraveling the mechanisms of nicotine addiction - Jiang, Jian; Li, Xia; Hu, An-fu; Zhou, Guo-jun; Gao, Yi-han; Xu, Chengyun; Wu, Xi-mei; Wang, Hong-Juan (Frontiers in Neuroscience, 2025)
Nicotine, recognized as the principal addictive component in tobacco, is mechanistically linked to its interaction with neuronal nicotinic acetylcholine receptors (nAChRs). nAChRs are ligand-gated ion channels composed of five transmembrane subunits, with the α4β2 receptor subtype being the most common in the brain, playing a crucial role in the behavioral effects of nicotine. When nicotine binds to α4β2 nAChR, it significantly enhances the firing rate and burst firing of dopamine neurons in the brain, thereby activating the mesolimbic dopamine system. This system promotes the formation of nicotine addiction in the early stages of addiction through rewarding sensory stimulation and associative learning. The α4β2 nAChR subunit has been identified as the principal subtype implicated in the pathogenesis of nicotine addiction. However, other nAChRs subtypes also play important roles in the onset and maintenance of nicotine addiction. Understanding the relationship between nicotine addiction and nAChR subtypes is crucial for fully uncovering the neurobiological mechanism behind its addictive properties and lays the foundation for developing more targeted smoking cessation strategies.